Presence of the Endangered Amur tiger Panthera tigris altaica in Jilin Province, China, detected using non-invasive genetic techniques. Issue 4 (14th January 2015) - Caragiulo, Anthony; Kang, Yang; Rabinowitz, Salisa; Dias-Freedman, Isabela; Loss, Simone; Zhou, Xu-Wei; Bao, Wei-Dong; Amato, George
Abstract: China is home to three subspecies of tiger Panthera tigris but there are no estimates of the size of any of the populations. We detected a population of the Endangered Amur tiger Panthera tigris altaica in Hunchun Nature Reserve in Jilin Province using both mitochondrial DNA and nuclear microsatellite loci. Four male and one female tigers were detected, indicating the potential for a small breeding group. However, genetic diversity was low overall, with six loci showing a heterozygote deficiency and a mean of 2.55 alleles per locus. This study is the first estimate of the wild Amur tiger population in China to use non-invasive techniques, and the presence of a female tiger indicates this is a potentially viable population. We provide baseline genetic diversity estimates to support monitoring of the population. The small number of tiger scats located indicates the importance of continuing the current conservation efforts for this tiger subspecies in Hunchun Nature Reserve. Such efforts include reducing poaching of tigers and their prey, and implementation of management plans to encourage the persistence and recovery of tigers in this area.